Evaluation of exotic barley genotypes for adaptation, yield and its component traits under irrigated conditions of North West India - Grewal, Purnoor Singh; Kaur, Simarjit (Journal of Cereal Research, 2018)
Field evaluation of 24 exotic barley (Hordeum vulgare L.) genotypes for adaptation, yield and its component traits along with two national checks BH946 (six-row) and DWRUB52 (two-row) was carried out at Punjab Agricultural University, Ludhiana, Punjab, India under irrigated conditions over two crop seasons 2014-15 and 2015-16. Temperature and precipitation prevailing during two crop seasons significantly influenced all the parameters except grains per spike, ear length, and 1000-grain weight. High rainfall resulted in significant crop lodging (20-100% lodging) during the year 2014-15 in genotypes IBYT 2, 5, 6, 11,14, 16, 17, 19, 20, 21, 24 and check BH946 which caused significant yield reduction. High temperature during 2015-16 caused a significantÂ reduction in phenological stages such as days to heading, days to maturity in all genotypes. Grain filling period, which is a major factor responsible for bold grains, also reduced in all the genotypes except IBYT 1, 2 and 23. Two entries, IBYT 14 and IBYT 21 were significantly earlier in heading than the best check DWRUB52 (94.3 days) by 5 days and 3 days, respectively. Exotic genotype IBYT4 is also a short-stature (96.3 cm height) genotypes, performed well for tiller number per meter, grains per spike and ear length. Genotype IBYT 18 possessed desirable values for grains per spike and 1000-grain weight. All exotic genotypes produced significantly lower grain yield (2.1-4.3 t/ha) than check DWRUB52 (4.9 t/ha). Six exotic genotypes (IBYT 18, IBYT 5, IBYT 7, IBYT 20, IBYT 21 and IBYT 23) with grain yield at par with check BH946 (3.9 t/ha) were identified and may be used in the breeding programme for widening the genetic base of six rowed barley germplasm.Â Doi.org/10.25174/2249-4065/2018/83436